Oil removal from oily sludge using surfactant technology - S.W, Puasa; K.N, Ismail; N.S.A, Rahim (International Journal of Engineering & Technology, 2018)
Surfactant technology is identified as one of the treatment methods that can be used for oil recovery from oily sludge. In this study, sodium lauryl ether sulfate (SLES) was used as the surfactant and its effectiveness was investigated. Several parameters involved in the study were SLES-to-oil sludge wastewater (OSW) volume ratio ranging from 0.17:1 to 1:1 and reaction time of 10 to 30 minutes. Results shows that the best condition for the percentage of loss of oil content (LOC) using SLES obtained was 59.87% at reaction time of 20 minutes and SLES/OSW ratio of 0.25. The experimental data were plotted using multilinear regression via Excel software. The value of R2 and adjusted R2 obtained for percentage of loss of moisture content (LMC) were 0.29 and 0.20, respectively which indicate the data are not well fitted. However, good data fitted was observed for percentage of LOC where R2 and adjusted R2 obtained were 0.973 and 0.1893, respectively. The ANOVA analysis shows that significance F and probability value for obtained all variables are less than 0.05 which proved the mathematical expression of LOC can be used to predict the loss of oil content from oily sludge.Â Â